2008
DOI: 10.1007/s00792-008-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of engineered amylopullulanase from Thermoanaerobacter ethanolicus 39E-implicating the non-necessity of its 100 C-terminal amino acid residues

Abstract: The functional and structural significance of the C-terminal region of Thermoanaerobacter ethanolicus 39E amylopullulanase (TetApu) was explored using C-terminal truncation mutagenesis. Comparative studies between the engineered full-length (TetApuM955) and its truncated mutant (TetApuR855) included initial rate kinetics, fluorescence and CD spectrometric properties, substrate-binding and hydrolysis abilities, thermostability, and thermodenaturation kinetics. Kinetic analyses revealed that the overall catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Little is known about the function(s) of FNIII domains in amylases. Published reports about FNIII domains in carbohydrate-acting enzymes do not show a clear common function, with results pointing at possible roles in substrate binding or enzymatic activity (38)(39)(40)(41)(42)(43). So far, there are no reports of FNIII domains in prokaryotes with a function in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the function(s) of FNIII domains in amylases. Published reports about FNIII domains in carbohydrate-acting enzymes do not show a clear common function, with results pointing at possible roles in substrate binding or enzymatic activity (38)(39)(40)(41)(42)(43). So far, there are no reports of FNIII domains in prokaryotes with a function in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, removal of only the CBM usually affects activity on insoluble substrates [15,16,[34][35][36][37][38][39][40], while the additional removal of the FNIII domains showed no further effects. In a study of the chitinase A1 from Bacillus circulans WL-12a, the single CBM present was re-attached after removal of one or two intermediate FNIII domains, allowing a direct test for the FNIII function [14].…”
Section: Fniii Domains Function Mainly As Stable Linkersmentioning
confidence: 92%
“…Both enzymes produced the same hydrolysis product profile of maltose and maltotriose from these substrates, respectively (Fig. 3, Lin et al 2008). The optimum pH of 6.0 for both amylase and pullulanase activity and the optimum temperature of 75°C were determined for both enzymes (data not shown).…”
Section: Domain Structures Of Tetapuq818 and Its Biochemical Charactementioning
confidence: 98%
“…Previously, truncation mutagenesis analyses of TetApu have revealed that the enzyme active region was within the TetApu R855 molecule Lin and Leu 2002;Lin et al 2008). In this study, further C-terminal truncated molecules such as TetApuQ818, TetApuG809 and TetApuK791, were constructed by PCR mutagenesis techniques and were expressed by the heterologous E.coli-pET expression system.…”
Section: Domain Structures Of Tetapuq818 and Its Biochemical Charactementioning
confidence: 99%
See 1 more Smart Citation